A Lifecourse Perspective of Intimate Partner Violence in India: What Picture Does the NFHS-3 Paint? - Heilman, Brian P. (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: The third National Family Health Survey of India has provided India with its first ever nationally representative data on domestic violence against women. This paper applies a lifecourse perspective to that data in order to understand how and when the major risk factors for intimate partner violence enter the lives of Indian women. Based on survey data, it finds that a preponderance of strong risk factors enter a woman's life very early. These factors include: childhood experience of violence, woman's justification of violence, husband's alcohol use, and husband's controlling behavior. The paper also uses a series of nonlinear probit regressions to compare the relative strength of the risk factors presented by the survey data. Holding the findings of its lifecourse perspective and regression equations against a relevant literature review, the paper concludes that the "picture" of intimate partner violence presented by this new survey data is improved but incomplete. Most critically, the lifecourse perspective presented in this paper highlights the fact that the survey fails to account adequately for major transitions in the life of a woman. These transitions include adolescence and the movement from "young bride" to "mother-in-law" status. The paper provides concrete suggestions for how a more nuanced attention the changing dynamics of life stages in the Indian woman's life can increase the value and accuracy of "pictures" of violence produced by future versions of the National Family Health Survey.